Biblioteca de Juan de Segovia : edición y comentario de su escritura de donación - Hernández Montes, Benigno (Madrid : Consejo Superior de Investigaciones Científicas, Instituto "Francisco Suárez", 1984., 1984)
323 pages, 8 unnumbered leaves of plates : facsimiles, portrait ; 25 cm
Spanish and Latin.;Includes indexes.